Réponse :
Explications étape par étape
a)
b)
c)
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Réponse :
Explications étape par étape
a)![E=3x^{2}+2*3x*2+2^{2}-(3x^{2}+21x+2x+14) E=3x^{2}+2*3x*2+2^{2}-(3x^{2}+21x+2x+14)](https://tex.z-dn.net/?f=E%3D3x%5E%7B2%7D%2B2%2A3x%2A2%2B2%5E%7B2%7D-%283x%5E%7B2%7D%2B21x%2B2x%2B14%29)
b)![E=(3x+2)[(3x+2)-(x+7)] E=(3x+2)[(3x+2)-(x+7)]](https://tex.z-dn.net/?f=E%3D%283x%2B2%29%5B%283x%2B2%29-%28x%2B7%29%5D)
c)![E=(3*\frac{1}{2}+2)^{2}-(3*\frac{1}{2})(\frac{1}{2}+7) E=(3*\frac{1}{2}+2)^{2}-(3*\frac{1}{2})(\frac{1}{2}+7)](https://tex.z-dn.net/?f=E%3D%283%2A%5Cfrac%7B1%7D%7B2%7D%2B2%29%5E%7B2%7D-%283%2A%5Cfrac%7B1%7D%7B2%7D%29%28%5Cfrac%7B1%7D%7B2%7D%2B7%29)